Usaha Ternak Ayam Sentul Berbasis Indigofera zollingeriana di Kabupaten Indramayu - Asep Suherman; Yudhi Mahmud; Wiwik Ambarsari (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
This study aims to look at the prospects of Sentul chicken farming based on indigofera zollingeriana in Indramayu Regency. This research was conducted from September 2017 to January 2018 in Longok Village, Sliyeg District, Indramayu Regency. The research method was carried out by research with a quantitative descriptive approach. The research was carries out by livestock business analysis to benefit, efficiency, and break event point. The results of the study is very prospective with sales exceeding the break event point value of the number of Sentul chicken units in each treatment based on Indigofera, sp especially in the treatment of R5 ration (more than 69 tail) which gives the highest business feasibility.